A porous polycrystalline NiCo2Px as a highly efficient host for sulfur cathodes in Li–S batteries. Issue 40 (7th October 2021) - Wang, Lu; Zhang, Meng; Zhang, Bo; Wang, Bin; Dou, Jianmin; Kong, Zhen; Wang, Chunsheng; Sun, Xiuping; Qian, Yitai; Xu, Liqiang
Abstract : A porous polycrystalline NiCo2 P x with olivary morphology is firstly fabricated combining phosphorization and solvothermal method, and the obtained NiCo2 P x enables fast electrochemical reactions at the triple-phase interfaces for the sulfur cathode. Abstract : Metal phosphides have exhibited great potential in the construction of highly efficient sulfur cathodes, benefiting from their high conductivity and catalytic property, which have been utilized to improve sulfur utilization, inhibit the drain of sulfur species during long-term cycling and facilitate the kinetics of the electrochemical reactions at the sulfur cathode of Li–S batteries. Here, porous polycrystalline NiCo2 P x with an olivary morphology and robust structure has been fabricated via a facile derivation method. The NiCo2 P x -derived sulfur cathode exhibited superior performance compared with the NiCo2 O4 counterpart; besides high rate performance with a capacity of 610 mA h g −1 at 1C under an areal sulfur loading of 4.35 mg cm −2, areal capacity up to 8.54 mA h cm −2 was also achieved with high mass loadings of sulfur (5.79 mg cm −2 ) and a lean electrolyte (6 μL mg −1 ). The high conductivity and featured porous structure of NiCo2 P x is considered to facilitate the electrochemical and kinetic behavior of the sulfur cathode, and its high catalytic activity was also preliminary established based on analyses of CV, EIS and symmetric batteries measurement. This work provides a new strategy for the fabrication of phosphides of elements in the iron family, broadens the application of metal phosphides in Li–S batteries, and deepens the understanding of the correlation between the morphology/phase structure of metal phosphides and the electrochemical performance of sulfur cathodes.